2021
DOI: 10.1101/2021.04.30.442194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein induces brain pericyte immunoreactivity in absence of productive viral infection

Abstract: COVID-19 is a respiratory disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). COVID-19 pathogenesis causes vascular-mediated neurological disorders via still elusive mechanisms. SARS-CoV-2 infects host cells by binding to angiotensin-converting enzyme 2 (ACE2), a transmembrane receptor that recognizes the viral spike (S) protein. Brain pericytes were recently shown to express ACE2 at the neurovascular interface, outlining their possible implication in microvasculature injury in COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…We detected appreciable ACE2 messenger RNA and protein in PLCs cultured two-dimensionally compared with cultured human neural precursors (Extended Data Fig. 1a-d) 14,21 . To assess SARS-CoV-2 PLC tropism, we exposed PLCs to authentic SARS-CoV-2 at a multiplicity of infection (MOI) of 0.5, then collected the supernatant and cells daily (Fig.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…We detected appreciable ACE2 messenger RNA and protein in PLCs cultured two-dimensionally compared with cultured human neural precursors (Extended Data Fig. 1a-d) 14,21 . To assess SARS-CoV-2 PLC tropism, we exposed PLCs to authentic SARS-CoV-2 at a multiplicity of infection (MOI) of 0.5, then collected the supernatant and cells daily (Fig.…”
mentioning
confidence: 93%
“…SARS-CoV-2 can utilize angiotensin-converting enzyme 2 (ACE2) as a receptor, although other receptors have been proposed 9,10 . Recent studies on single-cell RNA sequencing (scRNA-seq) datasets indicated low levels of ACE2 expression in brain cells; however, expression is relatively high in some neurovascular unit (NVU) components, particularly in brain pericytes [11][12][13][14] . Autopsy series have suggested the potential for SARS-CoV-2 to spread throughout the brain, especially within vascular and immune cells.…”
mentioning
confidence: 99%
“…To understand the biology of these new viruses, organoids can serve as an experimental virology platform . Wang et al used brain organoids to determine whether SARS-CoV-2 infection affects the central nervous system. , It is known that SARS-CoV-2 enters cells via angiotensin-converting enzyme 2 (ACE2) receptor and ACE2 expression is relatively high in brain pericytes. To identify if SARS-CoV-2 has tropism to the brain pericyte, the cortical organoid was cocultured with pericyte-like cells and exposed to SARS-CoV-2. The cortical organoid without coculture showed little evidence of infection, but organoids cultured with pericyte-like cells exhibited infection with SARS-CoV-2, demonstrating that the pericyte-like cells in the cortical organoid acted as “viral replication hubs” mediating virus spread and the inflammatory response.…”
Section: Applications Of Brain Organoids For Disease Modeling and Dru...mentioning
confidence: 99%